Traumatic Isolated Trapezium Dislocation without Fracture: A Case Report and Review of the Literature - Robert M. Kenyon; Enda G. Kelly; Benny Padinjarathala (Case Reports in Orthopedics)
Isolated dislocation of the trapezium is an uncommon injury. There are sixteen cases to date reported in the literature. The management of these cases has varied from complete excision to open or closed reduction, with or without percutaneous wiring. This paper presents a case of an isolated dislocation of the trapezium without fracture, managed with closed reduction and percutaneous wiring, resulting in a good functional outcome.